2012
DOI: 10.1128/jcm.06815-11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Excretion Dynamics and Genotypic Characteristics of Rotavirus A during the Lives of Pigs Raised on Farms for Meat Production

Abstract: To determine the excretion dynamics and genotypic characteristics of rotavirus A (RVA), a longitudinal observational study was performed in 10 pigs from 3 litters at a farrow-to-finish farm. A total of 400 fecal samples were directly collected from the rectums of individual pigs (aged 7 to 217 days) at 3- to 14-day intervals. Seventy-one samples (17.5%) were positive for RVA by reverse transcription-PCR designed to detect the VP7 and VP4 genes. At least 13 combinations of 5 G (G2, G4, G5, G9, and G11) and 6 P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
3
7
1
Order By: Relevance
“…Four rotavirus VP7 genotypes (G2, G3, G4 and G5) and three VP4 genotypes (P[6], P[7] and P[32]) were detected on the study farm and almost every combination of these genotypes was found over the 2 years. This extent of genetic heterogeneity is similar to that described in similar studies of GARV on pig farms in other countries ( Amimo et al, 2013 , Lachapelle et al, 2014 , Miyazaki et al, 2013 , Miyazaki et al, 2012 ).…”
Section: Discussionsupporting
confidence: 87%
“…Four rotavirus VP7 genotypes (G2, G3, G4 and G5) and three VP4 genotypes (P[6], P[7] and P[32]) were detected on the study farm and almost every combination of these genotypes was found over the 2 years. This extent of genetic heterogeneity is similar to that described in similar studies of GARV on pig farms in other countries ( Amimo et al, 2013 , Lachapelle et al, 2014 , Miyazaki et al, 2013 , Miyazaki et al, 2012 ).…”
Section: Discussionsupporting
confidence: 87%
“…These results are in accordance with the findings of a previous study (10). Furthermore, asymptomatic rotavirus infections in pigs have caused concern, as rotaviruses are excreted from subclinically infected animals and can cause diarrheal outbreaks in herds (11,12). The novel primers used (Table 1) were advantageous for the molecular characterization of the rotaviruses in the samples.…”
supporting
confidence: 89%
“…The P [23] genotype has been described as predominant in Thailand (16,32) and was isolated from a pig in China (33). Pigs are regarded as important reservoirs for human rotavirus diversification (10,12,28,34). A study comparing rotavirus genotypes and the pathogenicity and virulence caused by amino acid indels is required for a broader understanding of the infections caused by rotaviruses.…”
mentioning
confidence: 99%
“…Another explanation for the higher genetic diversity in the pig genes might be the existence of a stronger evolutionary drift in pig RVAs than in human RVAs. This is not unlogical, as pigs repeatedly come into contact with different rotavirus strains during the intense production stages (35,36).…”
Section: Discussionmentioning
confidence: 99%